Emergency department visits following total joint arthroplasty: do revisions present a higher burden?. (7th July 2022) - Singh, Vivek; Anil, Utkarsh; Kurapatti, Mark; Robin, Joseph X.; Schwarzkopf, Ran; Rozell, Joshua C.
Abstract : Aims: Although readmission has historically been of primary interest, emergency department (ED) visits are increasingly a point of focus and can serve as a potentially unnecessary gateway to readmission. This study aims to analyze the difference between primary and revision total joint arthroplasty (TJA) cases in terms of the rate and reasons associated with 90-day ED visits. Methods: We retrospectively reviewed all patients who underwent TJA from 2011 to 2021 at a single, large, tertiary urban institution. Patients were separated into two cohorts based on whether they underwent primary or revision TJA (rTJA). Outcomes of interest included ED visit within 90-days of surgery, as well as reasons for ED visit and readmission rate. Multivariable logistic regressions were performed to compare the two groups while accounting for all statistically significant demographic variables. Results: Overall, 28, 033 patients were included, of whom 24, 930 (89%) underwent primary and 3, 103 (11%) underwent rTJA. The overall rate of 90-day ED visits was significantly lower for patients who underwent primary TJA in comparison to those who underwent rTJA (3.9% vs 7.0%; p < 0.001). Among those who presented to the ED, the readmission rate was statistically lower for patients who underwent primary TJA compared to rTJA (23.5% vs 32.1%; p < 0.001). Conclusion: ED visits present a significant burden to the healthcare system. Patients who undergo rTJA are more likely to present to the ED within 90 days following surgery compared to primary TJA patients. However, among patients in both cohorts who visited the ED, three-quarters did not require readmission. Future efforts should aim to develop cost-effective and patient-centred interventions that can aid in reducing preventable ED visits following TJA. Cite this article: Bone Jt Open 2022;3(7):543–548.